A continuous‐effect membrane distillation process based on hollow fiber AGMD module with internal latent‐heat recovery. Issue 4 (13th September 2012) - Yao, Kun; Qin, Yingjie; Yuan, Yingjin; Liu, Liqiang; He, Fei; Wu, Yin
<x xml:space="preserve">Abstract</x> A continuous‐effect membrane distillation (CEMD) process was developed by equipping air gap membrane distillation (AGMD)‐based and strictly‐parallel hollow fiber module with internal heat recovery. Its performance was indicated by flux, performance ratio and evaporation efficiency. Two kinds of CEMD modules made from different membrane fibers were tested. A face‐centered central composite experimental design was conducted to investigate the influences of operating variables including cold‐feed temperature, hot‐feed temperature, and feed‐in flow rate on the performance. Within the studied experimental range, the maximum PR of 13.8 was obtained. A theoretical model based on governing transport equations was established to predict the process performance, and the model described the experimental data fairly well. In light of the model, possible ways to further increase PR were predicted. The dilute aqueous sugar solution was successfully concentrated 12‐fold to a final concentration of about 20 wt % by using CEMD process with a final PR of 8.2. © 2012 American Institute of Chemical Engineers AIChE J, 59: 1278–1297, 2013